Response of Groundnut (Arachis hypogaea L.) Varieties to Critical Period of Crop-Weed Interference in West Coast Region of The Gambia - S.A.F. Jallow; F.J. Manneh (European Scientific Journal, ESJ, 2025)
Field trials were conducted in the 2021 rainy season at the National Agricultural Research Institute Banjulinding (NARI Site III) and the Teaching and Research Farm of the University of The Gambia (UTG Faraba Banta). The study aimed to determine the critical period of crop-weed interference on weed attributes, growth and yield of groundnut varieties. Hence, the objective was to determine a specific timeframe critical for weed management as well as growth and yield responses of the two groundnut varieties (Fleur 11 and Philippine pink) to weed competition.  The experiment was conducted in a Randomized Complete Block Design with Nine (9) treatments replicated three times. The treatments tested were as follows:  Weed-free up to 21 DAS, Weed-free up to 42DAS, Weed-free up to 63DAS, Weed-free check (75DAS), Weed Infestation up to 21DAS, Weed Infestation up to 42 DAS, Weed Infestation up to 63 DAS, Weedy check. The Groundnut variety used as a test crop was Fleur 11. The results revealed that weed-free check (75 DAS) recorded the highest mean weed control efficiency (98.3 %) and lowest percentage of weed infestation (22.0%) followed by Weed-free up to 63DAS with 85% weed control efficiency and 39% weed infestation in both locations. The critical period for crop-weed interference in the groundnut variety tested was observed to be between 21 DAS to 63 DAS. The mean pod yield of the groundnut varieties was found to increase from 769kg/ha at 21 DAS to 967kg/ha at 63 DAS with a decrease in weed density in both trials. The weedy situation was found to decline the pod yield of the groundnut varieties by 58% to 87% in Site III and UTG Faraba, respectively.